A review of the latest research on SDN technology optimization - IAOZiyu X (Dianxin kexue)
Under the background of SDN technology from the college to commercial,the research results of OpenFlow protocol optimization,application oriented flow table design,SDN multi-domain control,data center network routing optimization and requirements of security network architecture were introduced and summarized.At last,the application scenarios and research directions for the future SDN technology was proposed.